Efektivitas Pengadilan Litigasi dalam Penyelesaian Sengketa Bisnis - Rosalina, Finna Rosalina (EL-EMIR Institute, 2024)
This article discusses business disputes through litigation. Litigation is the process of resolving disputes through court. Choosing the right resolution path is very important to resolve business disputes well without causing excessive harm to either party. This research uses a library study approach, namely a research method that relies on books and other library sources as the main material and data. The research results explain that resolving business disputes through court is a method that is often used when the parties involved cannot reach an agreement through negotiation or mediation. Once the judge makes a final decision, the losing party must comply with the decision. This is a formal way to resolve disputes, and the process can involve various stages such as the presentation of evidence, a court hearing, and a judge's assessment. The District Court is part of the justice system which has the duty and authority to handle criminal and civil cases at the first instance. The Commercial Court is a special type of court which is also within the general court environment. The Commercial Court has special duties and authorities related to bankruptcy cases and payment delays.